Shear response of ultra-lightweight CFRP cores. (15th April 2020) - Vitale, Pablo; Francucci, Gaston; Rapp, Helmut; Stocchi, Ariel
Abstract: In this work the shear performance of ultra-lightweight (ULW) carbon fiber reinforced polymer (CFRP) cores with 3-dimensional (3D) geometries is analyzed. The cores are made from a machined CFRP laminate. Using the interlocking method, CFRP sheets are assembled in order to obtain a square pattern. The density of all manufactured cores is achieved below than 48 kgm −3 . Through simple analytical mechanical models, it is possible to predict the failure behavior of the panels. Finite element analyses (FEA) are carried in order to contrast and validate the theoretical models. Good agreement among theoretical, finite element and experimental results is found. The experimental results show that the controlling failure mechanisms are shear failure of the base material or debonding, also predicted successfully by the numerical and analytical approaches. Finally, the cores are compared favorably as well with other competing known materials.